Pelatihan Pemanfaatan Tempat Sampah Otomotis di Kampung Pulosari - Gaguk Suprianto; Rr. Iramani; Titis Puspitaningrum (Jurnal Pengabdian kepada Masyarakat, 2024)
Waste management is a serious problem in densely populated environments. This research examines community service efforts aimed at overcoming waste management problems in Pulosari Village, Surabaya, through the application of the automatic trash can concept. By using survey, preparation, implementation and evaluation methods, this program was successful in installing automatic trash cans, holding outreach to the community, as well as providing assistance and evaluation on the use of these automatic trash cans. The automatic trash bin created is capable of detecting metal and non-metal waste and sorting it automatically. The results show a positive response from society towards this technological innovation, with increased awareness of the importance of keeping the environment clean. However, further evaluation is still needed to improve the effectiveness and sustainability of this program in the future. Therefore, this activity participates in efforts to create a cleaner, healthier and more sustainable environment in Pulosari Village and can be used as an example for other villages or villages in overcoming similar problems.